Contesting conservation-planning: insights from Ireland since independence. (2nd January 2020) - Parkinson, Arthur; Scott, Mark; Redmond, Declan
ABSTRACT: Where conservation evolves in contentious political contexts, it can be framed by competing priorities reflecting collective remembering, cultural politics and identities intertwined with the symbolic representation of the built environment. Ireland provides a unique lens to examine these themes as the only western European country to experience colonial domination, which forms a key aspect of the context for the evolution of conservation policy and practice. The aim of this paper is to chart the shifting representations of built heritage in Ireland, and their relevance in the emergence of conservation and heritage policy, set in the context of broader social, political and economic change over time. This is achieved, firstly, by a review of secondary source material to identify key events, eras and trends. Discourses of heritage are then examined in debates of the Oireachtas (the Irish legislature), identifying tensions around the emergence of conservation in a historic environment largely associated with colonial power and identity. These shifting discourses are then related to policy evolution, particularly the late adoption of a legislative framework for conservation (in 1999). Finally, conclusions are developed to identify wider lessons from the production of urban conservation priorities in the context of contested heritage.